Peran Jam’iyah Shalawat Seribu Rebana dalam Pembinaan Kecerdasan Spiritual Remaja Desa Mayangan Jogoroto Jombang - A. Syafi' AS. (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2019)
Jam'iyah shalawat seribu rebana does not only contain the concept of da'wah but also seeks to play a role in fostering the spiritual intelligence of adolescents to develop the intelligence potential of adolescents through positive behaviors. This study aims to describe the role of Jam'iyah Shalawat Seribu Rebana in fostering the spiritual intelligence of the youth of the village of Mayangan Jogoroto Jombang. This type of research is qualitative, using a descriptive approach. The data collection technique uses observation, interviews and documentation along with the sources related to the problem. The results of the research show that Jam'iyah Shalawat Seribu Rebana is a collective media of da'wah, with material in the form of the Qur'an, the Mawlid Diba Book 'and da'wah media in the form of banjari musical instruments. Jam'iyah Shalawat Seribu Rebana plays an important role in fostering the spiritual intelligence of Mayangan Jogoroto Jombang adolescents, so as to be able to create adolescents who have moral character.